PENJUALAN DAN PIUTANG USAHA TERHADAP PROFITABILITAS - Yanti, Meri; Nurrahman, Shadella; Safitri, Ningsih (Komunitas Manajemen Kompetitif, 2025)
Profitability is one of the key indicators in assessing a company's financial performance, particularly for distribution companies that rely on sales effectiveness and accounts receivable management. This research aims to analyze the influence of sales and accounts receivable on profitability at CV. Dima Mandiri Sejahtera. Specifically, this study examines the significant influence of sales on profitability, the significant influence of accounts receivable on profitability, and the simultaneous significant influence of sales and accounts receivable on company profitability. The study population consisted of 476 stores, with a sample of 134 obtained through purposive sampling and non-probability sampling techniques. The research approach uses a quantitative method with a ratio measurement scale. Data was obtained from the company's sales and accounts receivable reports, which were then analyzed using the Statistical Product and Services Solution (SPSS) version 22 application. The research results indicate that sales have a more significant impact on profitability compared to accounts receivable. Meanwhile, the influence of accounts receivable on profitability was found to be smaller. This finding indicates that improved corporate profitability can be achieved by strengthening sales activities and more efficiently managing receivables to maintain cash flow stability.